2010
DOI: 10.1007/s10600-010-9674-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the constituents of bulbs of the orchid Prosthechea michuacana and antioxidant activity

Abstract: 6), a known compound. The compounds were identified by spectral analysis and comparison with spectroscopic data reported in the literature. Compounds 3, 4, 5, and 6 showed DPPH and ABTS radicalscavenging and anti-lipid peroxidation activities, but none of the isolated triterpenes showed promising antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Some studies on this plant's properties reported relaxant and antispasmodic activity (Vargas-Solis & Perez-Gutierrez, 2009). In other scientific reports, its antiinflammatory and wound healing activity has been demonstrated (Perez-Gutierrez & Vargas-Solis, 2009a), and we found antioxidant activity in the constituents of the orchid bulbs (Perez-Gutierrez & Neira-Gonzales, 2010). In previous studies, we evaluated the hepatoprotective effects of a methanol extract of P. michuacana against paracetamol and carbon tetrachloride (CCl 4 )-induced hepatic damage in albino rats (Perez-Gutierrez & Vargas-Solis, 2009b).…”
Section: Research Articlesupporting
confidence: 70%
“…Some studies on this plant's properties reported relaxant and antispasmodic activity (Vargas-Solis & Perez-Gutierrez, 2009). In other scientific reports, its antiinflammatory and wound healing activity has been demonstrated (Perez-Gutierrez & Vargas-Solis, 2009a), and we found antioxidant activity in the constituents of the orchid bulbs (Perez-Gutierrez & Neira-Gonzales, 2010). In previous studies, we evaluated the hepatoprotective effects of a methanol extract of P. michuacana against paracetamol and carbon tetrachloride (CCl 4 )-induced hepatic damage in albino rats (Perez-Gutierrez & Vargas-Solis, 2009b).…”
Section: Research Articlesupporting
confidence: 70%
“…The family Orchidaceae is divided into 5 subfamilies, i.e., Epidendroideae, Orchidoideae, Vanilloideae, Cypripedioideae, and Apostasioideae [ 44 ]. So far, dimeric phenanthrenes have been reported from only two subfamilies, i.e., Epidendroideae (the genera Stanhopea, Bletilla, Pholidota, Pleione, Otochilus, Arundina, Bulbophyllum, Dendrobium, Monomeria, Cremastra, Agrostophyllum, Liparis, Cyrtopodium , Eria , Eulophia , Cirrhopetalum , Calanthe, Lusia, and Prosthechea ) and Orchidoideae (the genera Spiranthes and Gymnadenia ) [ 34 , 39 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. No biphenanthrenes have been found outside these two subfamilies.…”
Section: Resultsmentioning
confidence: 99%
“…The PE and EtOAc partitions were chromatographed over silica gel, Sephadex LH-20 and ODS columns, and semi-preparative HPLC to obtain eleven biphenanthrenes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) (Figure 1). Their structures were elucidated based on extensive spectroscopic analyses (Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…The phenanthrenes isolated thus far may be classified into three major groups: monophenanthrenes, biphenanthrenes, and triphenanthrenes, and most natural phenanthrenes occur in monomeric form [1]. To date, less than one hundred biphenanthrenes and two triphenanthrenes have been isolated from the Orchidaceae family [2][3][4][5][6][7][8][9][10][11][12][13]. Biphenanthrenes have been reported to possess various biological activities including cytotoxicity, antimicrobial, spasmolytic, anti-inflammatory, antiplatelet aggregation, and antiallergic activities [1].…”
Section: Introductionmentioning
confidence: 99%